A large-scale cross-country trial of WHO’s Immune Patrol: toward a game-based digital curriculum for vaccine readiness and global health education - Lieberoth, Andreas; Nielsen, Siff Malue; Reynen-de Kat, Catharina; Rotaru, Cristina; Niazyan, Lyudmila; Parandzem, Paryan; Craig, Brett Janson; Karstadt, Oscar Milsted; Demiscan, Daniela; Paraschiv, Angela; Gutu, Veaceslav (Frontiers in Education, 2025)
Vaccine-preventable diseases remain a global threat to public health, and despite the proven effectiveness of vaccines in protecting against these diseases, some people still avoid vaccinations for themselves or their children. Since barriers to protective health behaviors are diverse, overcoming them, and thereby reducing immunization gaps, necessitates diverse strategies. One such approach is to leverage health education through digital formats like online platforms and game-based learning, which can be implemented across geographical borders. We report a large-scale test of the World Health Organization’s Immune Patrol, a game-based middle school curriculum on vaccines and immunization. Using a matched quasi-experimental trial, classes in Armenia and the Republic of Moldova were exposed to local language versions of either five fully game-based lessons on topics including immunization, preventable diseases and digital source criticism, or non-game control materials on the same topics matching the digital and physical activities, without overt game elements. Significant learning outcomes were found across both countries, yet with differing gains among the classes within each country. Students assigned to game-based learning were slightly more motivated to learn about vaccine-preventable diseases, and to actively protect people around them through vaccination following the Immune Patrol experience. Qualitative observations highlight how practical and cultural differences can challenge homogenous implementation of learning packages like Immune Patrol across borders, but also how technology-enhanced collaborative classwork is welcomed in different ways across disparate classrooms. Results support the feasibility of global deployment of digital health education, but underscore the need for local support, and sensitivity to variations in culture, resources, teaching approaches and national education systems, when digital education initiatives like WHO’s Immune Patrol are set to transcend global borders.